Re-signification of "Cyprus" with the opening of new lines of communication - Arslan, Yetin (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: Cyprus has lived through important changes in the last decade. These changes have been, and are, influential in the re-construction of the meaning of the island and of things and peoples related to it. The ongoing de-linking and re-linking of new lines of communication results in the re-articulation of the meaning of all things “Cypriot.” Since 1974, communication between the two main communities on the island was limited as the two were separated not only with a border but with a wall as well. In the meantime, lines of communication have been changing. The significance and authority of the mass media of both sides have been diminished, and the meaning of their messages has been over-determined, with the opening of additional lines of communication. We can count the Internet and the World Wide Web, as well as the formation of bi-communal groups on the island among these. The last and, perhaps, most significant change has been the opening of the border gates on the island (23 April 2003) which allowed interaction and face-to-face communication between hitherto isolated communities. In my dissertation I study how the opening of these and other lines of communication have/are leading to a resignification of things and peoples related to Cyprus. I principally take the signifiers “Cyprus issue,” “peace,” “solution,” “European Union,” “Annan Plan,” “Turkish Cypriot,” “Greek Cypriot,” “Cypriot,” “Turkish,” “Greek,” and “European Cypriot” as cases, and observe both the temporal (from time to time) and spatial (from place to place) changes they are undergoing. The migration stories of Turkish Cypriots, their memories about the ‘home’, the ‘homeland’ and the re-turning ‘back’, the transfer of these stories from older generations to the youth and the experiencing of “new” Cyprus are also discussed in this dissertation. I performed textual analysis of the main newspapers in the Turkish Cypriot Print Media. These newspapers are; Kıbrıs, Halkın Sesi, Afrika, Yenidüzen and Birlik. However, my analysis is not limited to the representations of the printed text, but covers the representations in the social, historical, and cultural text as well. I, therefore, also look at bi-communal activities, demonstrations, web sites, and virtual communities. Keywords: communication, Cyprus, identity, representation, migration (displacement), memory and deconstruction. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Son on yılda Kıbrıs önemli değişimlere sahne oldu. Bu değişim, adanın ve onunla ilişkili şey/olay ve kişilerin anlamlandırılmasında etkili bir yeniden inşa sürecine girilmesine sebep oldu ve olmaya da devam etmektedir. İletişimin süregelen bağlantı koparıcı ya da bağlantı kurucu (bağları çözen ya da yeni bağlar yaratan) yeni kanalları, “Kıbrıslılığa” atfedilen tüm anlamlarda yeniden eklemlenmeler zinciri yarattı. 1974’ten beri iki toplum arasındaki iletişim sadece sınırın iki toplumu bölmesiyle değil aynı zamanda bir duvarla da sınırlandırılmıştı. Zaman içinde, toplumun sınırları/kanalları değişime uğradı ve uğruyor. Her iki taraftaki kitle iletişiminin önemi ve etkinliği azalırken, yaydıkları mesajların anlamı, iletişimin yeni kanallarının açılmasıyla belirlenir hale geldi. İnternet ve World Wide Web’i ve aynı zamanda adada iki toplumlu grupların oluşturulmasını bunlar arasında sayabiliriz. Ve son olarak da, belki de en önemli değişimi, adadaki, bugüne dek birbirinden kopmuş olan iki toplumda karşılıklı ve yüzyüze iletişimi mümkün kılabilecek sınır kapılarının açılmasını (23 Nisan 2003) saymalıyız. Doktora çalışmamda, açılan iletişim kanallarının Kıbrıs’la ilişkili şey/olay ve insanlara (toplumlara) dair nasıl bir yeniden-anlamlandırma sürecini tetiklediği üzerinde yoğunlaşıyorum. Esas olarak, “Kıbrıs sorunu”, “barış”, “çözüm”, “Avrupa Birliği”, “Annan Planı”, “Kıbrıslı Türk”, “Kıbrıslı Rum”, “Kıbrıslı”, “Türk” (“Türkiyeli”), “Rum” ve “Avrupalı Kıbrıslı” gibi gösterenleri ele alıp, bu kavramların hem zamansal olarak hem de mekansal olarak nasıl değiştiklerini gösteriyorum. Kıbrıslı Türklerin göç hikayeleri, “ev”e, “anayurda” ve geri “dönüş”e dair anıları, bu hikayelerin yaşlı kuşaktan genç kuşağa aktarımı ve bu “yeni” Kıbrıs’ın deneyimlenme biçimi de yoğunlaştığım konular arasında. Çalışmada Kuzey Kıbrıs yazılı basınındaki Kıbrıs, Halkın Sesi, Afrika, Yenidüzen ve Birlik gazetelerini metin çözümlemesi ile analize tabi tutuyorum. Ancak çalışmadaki analiz basındaki yazılı metinlerin temsili ile sınırlı değil; sosyal, tarihsel ve kültürel metinlerde ortaya çıkan temsiller de kapsama dahil. Ayrıca, iki toplumlu aktiviteler, gösteriler, web siteleri ve sanal topluluklar da bu bağlamda çalışmaya dahil. Anahtar Kelimeler: İletişim, Kıbrıs, kimlik, temsil, göç, hafıza ve yapısöküm.
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2012. Supervisor: Assoc. Prof. Dr. Tuğrul İlter.
Keywords: Communication and Media Studies; Intercultural Communication - Cyprus - Turks - Greeks; Intercultural Communication - Cross-Cultural Orientation - Turkish Cypriots - Greek Cypriots - Foreign Relations; Communication - Cyprus - Identity - Representation - Migration (Displacement) - Memory and Deconstruction